2013
DOI: 10.1159/000351435
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-Weighted Magnetic Resonance Imaging for Predicting and Detecting the Early Response to Chemoradiotherapy of Advanced Esophageal Squamous Cell Carcinoma

Abstract: Background: The aim of this study was to investigate the utility of the apparent diffusion coefficient (ADC) value in diffusion-weighted magnetic resonance imaging (DWMRI) for prediction and early detection of treatment response in advanced esophageal squamous cell carcinoma. Method: DWMRI was performed in 27 patients with primary cT4 esophageal carcinoma that were undergoing chemoradiotherapy before treatment and after 20 and 40 Gy. We calculated tumor ADCs and association of the treatment effect between resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 44 publications
2
42
0
Order By: Relevance
“…Liu et al reported the percentage ADC value change after 1 month correlated positively with size reduction after 2 months of chemoradiation in 17 patients with cervical cancer [27]. Another study reported the ADC value at the time of 20 Gy was significantly higher in responders compared to nonresponders in 27 patients with primary clinical T4 oesophageal carcinoma treated with chemoradiation [31]. We are planning a study to evaluate usefulness of DW-MRI in evaluation of the tumour response after SBRT and in distinction of treatment-related change from recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported the percentage ADC value change after 1 month correlated positively with size reduction after 2 months of chemoradiation in 17 patients with cervical cancer [27]. Another study reported the ADC value at the time of 20 Gy was significantly higher in responders compared to nonresponders in 27 patients with primary clinical T4 oesophageal carcinoma treated with chemoradiation [31]. We are planning a study to evaluate usefulness of DW-MRI in evaluation of the tumour response after SBRT and in distinction of treatment-related change from recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, MRI is increasingly used in the diagnosis and staging of gastric cancers . In particular, diffusion weighted imaging (DWI), which reflects the mobility of water molecules in vivo and is noninvasively quantified by apparent diffusion coefficient (ADC) values, has been investigated in various tumors …”
mentioning
confidence: 86%
“…[3][4][5][6][7] In particular, diffusion weighted imaging (DWI), which reflects the mobility of water molecules in vivo and is noninvasively quantified by apparent diffusion coefficient (ADC) values, has been investigated in various tumors. 8,9 Several studies have confirmed the value of DWI in detection 10 and characterization 11 of gastric cancers. MR imaging with DWI can increase the sensitivity and accuracy in TNM Classification of Malignant Tumors (TNM) staging of gastric cancers, 12,13 especially in T staging.…”
mentioning
confidence: 93%
“…Although MRI of the oesophagus is technically more challenging, owing to oesophageal motility and motion of the surrounding heart and diaphragm, advances in technology now enable the acquisition of high‐resolution magnetic resonance (MR) images. Previous studies on response prediction with MRI in oesophageal cancer focused on quantitative diffusion‐weighted (DW) MRI parameters. However, visual response assessment on T2‐weighted (T2W) and functional DW‐MRI in rectal cancer yielded higher sensitivity for detecting residual tumour compared with quantitative assessment.…”
Section: Introductionmentioning
confidence: 99%